2018
DOI: 10.1002/chem.201801298
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Ligand‐Centered Reduction in Low‐Coordinate Iron Formazanate Complexes

Abstract: Coordination of redox-active ligands to metals is a compelling strategy for making reduced complexes more accessible. In this work, we explore the use of redox-active formazanate ligands in low-coordinate iron chemistry. Reduction of an iron(II) precursor occurs at milder potentials than analogous non-redox-active β-diketiminate complexes, and the reduced three-coordinate formazanate-iron compound is characterized in detail. Structural, spectroscopic, and computational analysis show that the formazanate ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 107 publications
0
38
0
Order By: Relevance
“…[1][2][3] Formazanates have garnered considerable attention in coordination chemistry due to their ligand-based redox processes, which may facilitate multielectron redox transformations, [4] bond activations [5] and excited-state charge separation. [6] Av ariety of formazanate complexes of many main-group metals [7][8][9][10][11][12][13][14][15][16] andf irst-and second-row transition metals [17][18][19][20][21][22][23] have been described.T hese studies demonstrate the versatile coordination chemistry of formazanate ligandsa nd provides ignificant insight into the opticala nd redox properties of these compounds.S ome coppercomplexesc an also mediate oxygen activation, [24,25] certain cobalt and iron complexes exhibit unique magnetic characteristics, [17,26] and boronc omplexes in many cases feature not only the tunable redoxp roperties but also visible to nearinfrared photoluminescence, [9][10][11][12][13] finding applicationsa sc ellimaging agents [27,28] and electrochemiluminescence emitters. [10] Our group has expanded the coordination chemistry of formazanatest ot hird-row transition metals with as eries of hetero-leptic cyclometalated platinumc omplexes and bis-cyclometalated iridium complexes, [29][30][31] and accessed homoleptic azo-iminate platinum complexes and azo-1,2,3-triazolide iridium complexesv ia hydrogenative cleavage or [3+ +2]...…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Formazanates have garnered considerable attention in coordination chemistry due to their ligand-based redox processes, which may facilitate multielectron redox transformations, [4] bond activations [5] and excited-state charge separation. [6] Av ariety of formazanate complexes of many main-group metals [7][8][9][10][11][12][13][14][15][16] andf irst-and second-row transition metals [17][18][19][20][21][22][23] have been described.T hese studies demonstrate the versatile coordination chemistry of formazanate ligandsa nd provides ignificant insight into the opticala nd redox properties of these compounds.S ome coppercomplexesc an also mediate oxygen activation, [24,25] certain cobalt and iron complexes exhibit unique magnetic characteristics, [17,26] and boronc omplexes in many cases feature not only the tunable redoxp roperties but also visible to nearinfrared photoluminescence, [9][10][11][12][13] finding applicationsa sc ellimaging agents [27,28] and electrochemiluminescence emitters. [10] Our group has expanded the coordination chemistry of formazanatest ot hird-row transition metals with as eries of hetero-leptic cyclometalated platinumc omplexes and bis-cyclometalated iridium complexes, [29][30][31] and accessed homoleptic azo-iminate platinum complexes and azo-1,2,3-triazolide iridium complexesv ia hydrogenative cleavage or [3+ +2]...…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Holland and co-workers demonstrated that the energy of the LUMO can be decreased signicantly through the employment of the structurally related formazanate ligands, although strong reductants, as alkali metals, were still needed to induce ligand-centered reduction. [16][17][18] Quite surprisingly, the simple acetylacetonate ligand (acac ¼ monoanion of pentane-2,4-dione) has never been reported to participate in redox events in transition metal chemistry. The existence of an unstable Li + or Mg 2+ -bound anion radical, acacc 2À , generated by reduction with n-butyllithium or Grignard reagents, was suggested by EPR spectroscopy; however, it could not be isolated or studied in any further detail.…”
Section: Introductionmentioning
confidence: 99%
“…Mono-formazanate iron amide 20 or its THF adduct 20-THF were used to prepare the one-electron reduction product 21 (Scheme 7), which was studied using a variety of spectroscopic and computational techniques. 30 A multi-configurational quartet ground state was calculated for 21 using SORCI, which reproduces the empirical spectroscopic data. The calculations suggest two configurations to be dominant (ca.…”
Section: Group 8 (Fe Ru Os)mentioning
confidence: 93%